Feeling the pain of others is associated with self-other confusion and prior pain experience - Derbyshire, Stuart W.; Osborn, Jody; Brown, Steven (Frontiers in Human Neuroscience, 2013)
Some chronic pain patients and healthy individuals experience pain when observing injury or others in pain. To further understand shared pain, we investigated perspective taking, bodily ownership and tooth pain sensitivity. First, participants who reported shared pain (responders) and those who did not (non-responders) viewed an avatar on a screen. Intermittently, 0-3 circles appeared. Sometimes the participant's and avatar's perspective were consistent, both directly viewed the same circles, and sometimes inconsistent, both directly viewed different circles. Responders were faster than non-responders to identify the number of circles when adopting a consistent perspective. Second, participants sat with their left hand hidden while viewing a rubber hand. All participants reported an illusory sensation of feeling stroking in the rubber hand and a sense of ownership of the rubber hand during synchronous stroking of the rubber and hidden hand. The responders also reported feeling the stroking and a sense of ownership of the rubber hand during asynchronous stroking. For experiment three, participants with either low, moderate or high tooth sensitivity observed a series of images depicting someone eating an ice-popsicle. Low sensitivity participants never reported pain. In contrast, moderate and high sensitivity participants reported pain in response to an image depicting someone eating an ice popsicle (4% and 19% of the time, respectively) and depicting someone eating an ice-popsicle and expressing pain (23% and 40%, respectively). In summary, responders have reduced ability to distinguish their own and others' visual perspective and enhanced ability to integrate a foreign arm into their bodily representation. The tendency to share pain is also enhanced when an observed pain is commonly experienced by the observer. Shared pain may therefore involve reactivation of pain memories or pain schema that are readily integrated into a self perspective and bodily representation.